Identifying and managing interstitial cystitis. Issue 10 (October 2022) - Fish, Joanna; Boodramsingh, Marco; Wanis, Michael; Sornalingam, Sangeetha; Cooper, Max
Urological presentations are common in general practice. Many are straightforward presentations such as lower urinary tract infections. Nevertheless, GPs must always consider more serious causes, not least renal disease and cancer. A further challenge lies in unexplained, persistent or treatment-resistant symptoms, which may be associated with chronic pain. A key urological presentation that captures all of these is interstitial cystitis/bladder pain syndrome. This diagnosis of exclusion calls for thorough history taking, appropriate investigation, strategies to exclude sinister causes and management options for chronic symptoms.